Improving Science Literacy in Elementary Schools Through the Application of the RADEC Model - Nadiah Talita Putri; Wati Sukmawati (Jurnal Penelitian Pendidikan IPA, 2024)
This study evaluates the RADEC (Read, Answer, Discuss, Explain, and Create) learning method's impact on enhancing students' science literacy skills. By analyzing changes in question difficulty levels from pretest to posttest, the research assesses how effective RADEC is in improving students' comprehension of science concepts. The methodology involves administering questions before and after RADEC implementation, with statistical analysis revealing significant variations in question difficulty. Some questions became more challenging post-RADEC, indicating deeper understanding, while others remained stable or became easier, possibly due to improved familiarity or consistent teaching quality. Overall, RADEC promotes active engagement, sustains interest, and enhances understanding of science topics. The study underscores RADEC's efficacy in boosting science literacy, recommending its adoption in educational settings for optimal learning outcomes. It also highlights the need for appropriate evaluation tools in assessing students' responses to science education, offering valuable insights into effective teaching methodologies